Linguistic and Stylistic of the Qur'an in “Ayat al-Ahkam” Book by Shoiman Luqman Hakim l Al-Usalib al-Lughawiyah wal-Uslubiyah fi al-Qur'an fi Kitab Ayat al-Aḥkam li-l-Awsat Ṣa'iman Luqman Ḥakim - Munawaroh, Siti Madinatul; Milah, Aang Saeful; Asmara, Hilda Dimyati (Universitas Islam Negeri Raden Intan Lampung, 2024)
The Quran has its own characteristics compared to other books. There are many rhetorical and stylistic methods in the Al-Quran, but this research only discussed the book entitled “Ayatil Ahkam” as a guide to the Al-Quran because this book contains verses from the Quran that discuss certain topics, with selected legal verses which are divided into various subchapters in these themes. This research was a stylistic study of the Al-Quran, based on the theory of Abdul Azim al-Zarkani. The focus of this research was to analyze words that contain the form of command and prohibition, the researcher limited its scope. This article discussed the topic which was divided into three parts of “Ayat al-Ahkam”: the pillars of faith, the pillars of Islam, and worship. These three topics contain the stylistic language of the Quran in the form of commands and prohibitions. On the topic of the pillars of faith, there are 2 forms of imperative; In the pillars of Islam there are 5 forms of imperative; and in worship there are 22 forms of commands, 7 forms of prohibitions, in total there are 29 forms of imperatives and 7 forms of prohibitions both in verb and collective form. The stylistic analysis of the Qur'an at this stage focuses on the grammatical area. The contribution of this research is the discovery of new insights into verses containing imperative and prohibition that had not been identified previously, only analyzing shighah amr and nahy using research objects in one surah of the Quran.